Compression therapy following ambulatory phlebectomy - de Roos, K.-P.; Bruins, F. G.; Neumann, H. A. M. (Phlebologie, 2008)
Aim: The study was designed to evaluate the feasibility, results and safety of a very short period of compression after ambulatory phlebectomy. Patients, methods: From September to December 2006 we prospectively studied 49 subsequent patients who underwent ambulatory phlebectomy for branch varicose veins. Post-operatively the treated part of the leg was bandaged for forty-eight hours. Results: No major adverse events occurred. Although 46.9% of treated patients had visible haematomas two days post-operatively, after six weeks this was only visible in one patient. The results of this study show that the clinical outcome of ambulatory phlebectomy in combination with compression for forty-eight hours is at least equal to a conventional (longer) period of compression. Conclusion: Post-operative treatment can be safely reduced without the need of adjuvant compression hosiery. This will reduce patient discomfort after ambulatory phlebectomy without jeopardizing the clinical outcome.
Keywords: Varicose veins; ambulatory phlebectomy; compression therapy